2007
DOI: 10.1089/vbz.2007.0572
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Ectoparasite Intensities and Rabies Virus Neutralizing Antibody Seroprevalence in Wild Big Brown Bats (Eptesicus fuscus), Fort Collins, Colorado

Abstract: Recently, bat ectoparasites have been demonstrated to harbor pathogens of potential importance to humans. We evaluated antirabies antibody seroprevalence and the presence of ectoparasites in big brown bats (Eptesicus fuscus) sampled in 2002 and 2003 in Colorado to investigate if an association existed between ectoparasite intensity and exposure to rabies virus (RV). We used logistic regression and Akaike's Information Criteria adjusted for sample size (AICc) in a post-hoc analysis to investigate the relative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Constantine [71] suggested that some bats may be less susceptible to RV infection and those that develop the disease may be immunocompromised. It is of note that seronegative bats at our study area also had greater infestation by some ectoparasites than seropositive bats, perhaps correlated with greater stress [74]. Experiments demonstrated that wild seropositive bats can have immunity to experimental infection, and that experimental inoculation with a variant of RV found in our study population can lead to circulating RVNA without the disease [22], adding another dimension to the complexity of host-virus dynamics in this system.…”
Section: Discussionmentioning
confidence: 60%
“…Constantine [71] suggested that some bats may be less susceptible to RV infection and those that develop the disease may be immunocompromised. It is of note that seronegative bats at our study area also had greater infestation by some ectoparasites than seropositive bats, perhaps correlated with greater stress [74]. Experiments demonstrated that wild seropositive bats can have immunity to experimental infection, and that experimental inoculation with a variant of RV found in our study population can lead to circulating RVNA without the disease [22], adding another dimension to the complexity of host-virus dynamics in this system.…”
Section: Discussionmentioning
confidence: 60%
“…This is true for rabies, and the presence of rabies-neutralizing antibodies in the blood of healthy bats suggests that bats are more capable of surviving exposure to this disease than are other mammals (e.g. Shankar et al 2004, Pearce et al 2007). The lack of obvious die-offs due to rabies or other diseases in bats has the potential to give some researchers the false impression that infectious disease is a relatively unimportant source of mortality in bats.…”
Section: Rabiesmentioning
confidence: 99%